Improving Cognitive Abilities Through Playing Galabob Music Using Natural Materials Media for Children Aged 5-6 Years at Ainun Jonggol Preschool - Nila Febrianti; Agustin Hamidah; Roza Yenita (PT FORMOSA CENDEKIA GLOBAL, 2024)
Cognitive is not just a child's learning but strengthens the mental so that children can interact in the environment and can do their activities happily and confidently. Stimulation that can be used to improve cognitive is by playing music. In order to find out whether cognitive can be increased through music playing activities in children aged 5-6 years with the type of classroom action research to produce accurate data. Observation results of meeting I Cognitive ability criteria develop according to expectations (BSH) 10% begin to develop (MB) 30% and have not developed (BB) 60%. Observation results of meeting II cognitive ability criteria develop according to expectations (BSH) 10%, begin to develop (MB) 30% and have not developed (BB) 60%. Therefore, music can improve cognitive abilities in children aged 5-6 years at PAUD Ainun.